The Nicotinic Acetylcholine Receptor as a Target for Antidepressant Drug Development - Philip, Noah S. (The Scientific World Journal, 2012)
An important new area of antidepressant drug development involves targeting the nicotinic acetylcholine receptor (nAChR). This receptor, which is distributed widely in regions of the brain associated with depression, is also implicated in other important processes that are relevant to depression, such as stress and inflammation. The two classes of drugs that target nAChRs can be broadly divided into mecamylamine- and cytisine-based compounds. These drugs probably exert their effects via antagonism at α4β2 nAChRs, and strong preclinical data support the antidepressant efficacy of both classes when used in conjunction with other primary antidepressants (e.g., monoamine reuptake inhibitors). Although clinical data remain limited, preliminary results in this area constitute a compelling argument for further evaluation of the nAChR as a target for future antidepressant drug development.